Argon and krypton adsorption on templated mesoporous silicas: molecular simulation and experiment. - Thommes, Matthias; et al. (Adsorption-Journal of the International Adsorption Society, 2007)
Mol. simulation results for argon and krypton adsorption on atomistic models of templated mesoporous silica materials are reported. These models add atomistic levels of detail to mesoscale representations of these porous materials, which were originally generated from lattice Monte Carlo simulations mimicking the synthesis process of templated mesoporous silicas. The atomistic pore models were generated by carving out of a silica block a math.-smooth' representation of the pores from lattice MC simulations. Following that procedure, we obtain a model material with mean mesopore and micropore diams. of 5.4 nm and 1.1 nm, resp. (model A). Two addnl. model materials were considered: one with no microporosity, and with mesopores similar to those of model A (model B), and a regular cylindrical pore (model C). Simulation results for Ar and Kr adsorption on these model materials at 77 K and 87 K shows that model A provides the best agreement with exptl. data; however, the results suggest that fine-tuning the microporosity and/or the surface chem. (i.e., by decreasing the d. of OH groups at the pore surface) of model A can lead to better agreement with expts. The filling of the mesopores in model materials A and B proceeded via a classical capillary condensation mechanism, where the pores fill at slightly different pressures. This observation contrasts with what was obsd. in the previous study, where it were considered atomistic silica mesopores with an important degree of surface roughness at length scales <10 Å, for which a quasi-continuous mesopore filling was obsd. involving intermediate phases with liq.-like "bridges" and gas-like regions. Pore surface roughness, and other morphol. features such as constrictions, play an important role in the mechanism of adsorption and filling of the mesopores. [on SciFinder(R)]
Keywords: argon krypton adsorption mechanism simulation mesoporous silica